The effectiveness and nephrotoxicity of loading dose colistin combined with or without meropenem for the treatment of carbapenem-resistant A. baumannii - Wasan Katip (2020)
© 2020 The Author(s) Introduction: Acinetobacter baumannii has emerged as an important nosocomial pathogen worldwide. In Thailand, the incidence and mortality rate of carbapenem-resistant A. baumannii (CRAB) is continuously increasing. This organism is a common pathogen that can cause HAP and VAP. CRAB tends to be susceptible to only colistin, so colistin would be the last line of treatment for CRAB. The recent data from in-vitro studies found that colistin and meropenem combination therapy could exert synergistic effects. However, some in-vivo studies have shown no significant difference in antibacterial effect between colistin monotherapy and colistin plus meropenem. Moreover, the clinical data are recently limited and not clear. Thus, the objective of this study was to compare clinical outcome, microbiological response, mortality rate and nephrotoxicity between loading dose (LD) colistin monotherapy and LD colistin-meropenem for treatment of infection caused by CRAB in Maharaj Nakorn Chiang Mai Hospital. Materials and Methods: This study is a retrospective analytical study. The data were collected from patients who received LD colistin monotherapy or LD colistin plus meropenem combination therapy for treatment of CRAB from 1 January 2013 to 31 August 2017 at Maharaj Nakorn Chiang Mai Hospital. A total of 324 patients met the inclusion criteria. The data were analyzed by descriptive statistics and inferential statistics, and were adjusted for confounding factors by logistic regression analysis. Results: The adjusted OR of good clinical outcome of patients who received LD colistin plus meropenem was 1.05 times that of patients who received loading dose colistin monotherapy (95%CI 0.62-1.74, p = 0.860). Patients who received LD colistin plus meropenem had 0.93 times (adjusted OR) mortality rate at the end of treatment compared to patients who received LD colistin monotherapy (95%CI = 0.51-1.71, p = 0.935). In addition, microbiological response was defined as eradication of pre-treatment isolated pathogens in post-treatment cultures. Patients who received LD colistin plus meropenem could eradicate pathogens 1.28 times more than LD colistin monotherapy (95% CI = 0.74-2.20, p = 0.371). Also there was no significant difference in nephrotoxicity (adjusted OR = 0.84, 95% CI 0.52-1.36, p = 0.492) between LD colistin monotherapy and LD colistin plus meropenem. Conclusion: There were no significant differences in effectiveness and nephrotoxicity of LD colistin monotherapy versus LD colistin plus meropenem for treatment of CRAB infection, so colistin combination therapy was not necessary for the management of infection caused by CRAB.